THE INFLUENCE OF USING TIME TOKEN METHOD TOWARD SPEAKING ABILITY AT THE STUDENTS’ OF SMP N 1 BATANGHARI ACADEMICYEAR 2014/2015 - Retno Fentari; Syaifudin Latif Darmawan (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2016)
The objective of the study is to know whether there is influence of Time Token method toward students’ speaking ability. The research design of this research is Quantitative Design. The population of this research is 625 students. It consists of 21 classes and average of each class consists of 32 students. The researchers conducted the research at the eighth grade of SMP N 1 Batanghari. The researcher took 64 students from the total population as the sample. This research takes two classes: they are experimental class and control class. In Colleting the data, the researcher used test. The test comprised two tests: pre test and post test. To analyze data, the researcher used ttest formula. The result of the study showed that tcount5,37 and tdaf is 2,00 (on criteria1) and 2,66 (on criteria 2). It means that tcount >tdaf. And the criteria of tcount is Ha accepted if tcount>tdaf.